PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, JUMLAH PENDUDUK MISKIN, LUAS WILAYAH TERHADAP PERTUMBUHAN EKONOMI - Sherina Arum Pamukti; Andy Dwi Bayu Bawono (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Economic growth is one of the important indicators to analyze a national development that occurs in a country which is a major concern for the government. The existence of the Covid-19 pandemic has an impact on economic growth in Indonesia. The purpose of this research is to determine the effect of Regional Original Income, General Allocation Funds, Number of Poor Population, and Areas on Economic Growth in 2020, where data is recorded in the Directorate General of Fiscal Balance (DJPK) and the Central Statistics Agency (BPS) in 2020. Where obtained 514 regencies/cities. In collecting the sample, purposive sampling method was applied which then obtained 300 regencies/cities which were used as samples. Analysis of the data using multiple linear regression where the research results obtained, namely the Regional Original Income and General Allocation Funds affect economic growth, while the variables of the number of poor people and the size of the area do not affect economic growth.